A study on Economic impact assessment of chilli variety ‘Kashi Anmol’ - Pal, Govind; Roy, S.; Singh, Neeraj; Bahadur, Anant; Singh, P.M.; Rajesh Kumar (Vegetable Science, 2025)
ICAR-Indian Institute of Vegetable Research, Varanasi developed a chilli variety ‘Kashi Anmol’ in 2006. This variety has been widely adopted and cultivated by the farmers in different parts of the country. The present study helps in estimating the economic surplus generated as a consequence of research outputs for development of chilli variety ‘Kashi Anmol’. The approximate spread of area under Kashi Anmol variety was estimated at 163695.95 ha during 2005-06 to 2021-22 covering a total of 165 districts in 26 states. The Average chilli area in the Country was 391667 ha. during TE 2020-21. The annual average area under Kashi Anmol variety of chilli in the Country was 9629.17 ha. per annum. The estimated results of economic surplus model (ESM) showed that there was producer surplus of Rs. 11.94 crores, consumer surplus of Rs. 18.94 crores and total economic surplus of Rs. 30.88 crores generated from the variety. The Net Present Value (NPV) generated was Rs. 30.50 crores, Net Present Benefit (NPB) was Rs. 30.88 crores and Net Present Cost (NPC) was Rs. 38 Lakhs. The Internal Rate of Return (IRR) was 79 per cent and Benefit Cost Ratio (BCR) 81.22 in the present technology. The total cost of cultivation of Kashi Anmol variety of chilli was Rs. 221529 per hectare compared to Rs. 226139 per hectare of local variety. The net return in Kashi Anmol variety of chilli was Rs. 277971 per hectare while it was Rs. 213261 per hectare in local variety of chilli. The BC ratio was 2.26 and 1.94 for Kashi Anmol variety and local variety of chilli. The monetary value of break-even output estimated to Rs. 56865.32 for Kashi Anmol variety while it was Rs. 62814.76 for local variety. The present study indicates that the investments made for the development of Kashi Anmol variety of chilli was highly economical and provided evidence to the policy makers that supporting the research investment for the same.